Role of mTOR inhibitors for the control of viral infection in solid organ transplant recipients. Issue 6 (19th October 2016) - Pascual, Julio; Royuela, Ana; Fernández, Ana M.; Herrero, Ignacio; Delgado, Juan F.; Solé, Amparo; Guirado, Lluis; Serrano, Trinidad; de la Torre‐Cisneros, Julián; Moreno, Asunción; Cordero, Elisa; Gallego, Roberto; et al.
Abstract: Appropriate post‐transplant immunosuppressive regimens that avoid acute rejection, while reducing risk of viral reactivation, have been sought, but remain a chimera. Recent evidence suggesting potential regulatory and antiviral effects of mammalian target of rapamycin inhibitors (mTORi) is of great interest. Although the concept of an immunosuppressive drug with antiviral properties is not new, little effort has been made to put the evidence together to assess the management of immunosuppressive therapy in the presence of a viral infection. This review was developed to gather the evidence on antiviral activity of the mTORi against the viruses that most commonly reactivate in adult solid organ recipients: cytomegalovirus (CMV), polyomavirus, Epstein‐Barr virus (EBV), human herpesvirus 8 (HHV8), and hepatitis C virus (HCV). A rapid review methodology and evaluation of quality and consistency of evidence based on the GRADE system was used. The existing literature was variable in nature, although indicating a potential advantage of mTORi in CMV, polyomavirus, and HHV8 infection, and a most doubtful relation with EBV and HCV infection. Several recommendations about the management of these infections are presented that can change certain current patterns of immunosuppression and help to improve the prognosis of the direct and indirect effects of viral infection in solid organ recipients.